2019
DOI: 10.29252/ijn.32.117.69
|View full text |Cite
|
Sign up to set email alerts
|

The Association of the Quality of Work Life and General Health of the Nurses in Psychiatric Wards

Abstract: Background & Aims: The level of tension and stress is comparatively higher in psychiatric units due to the nature of the disorders and conditions of the patients under treatment, which could threaten various aspects of the general health of psychiatric nurses. Furthermore, this issue could adversely affect the quality of work life in nurses. The present study aimed to investigate the association between the quality of work life and general health of the nurses in the psychiatric wards of the teaching hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Additionally, happiness research can play an important role in strengthening relationships and bolstering a sense of community between people. Research showing that happiness increases when people are connected and support each other can contribute to strengthening social cohesion (Darbanastaneh & Mahmoudi, 2016;Esmaeilpour & Jafarjalal, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, happiness research can play an important role in strengthening relationships and bolstering a sense of community between people. Research showing that happiness increases when people are connected and support each other can contribute to strengthening social cohesion (Darbanastaneh & Mahmoudi, 2016;Esmaeilpour & Jafarjalal, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines general health as "a state of mental well-being that enables people to cope with the stresses of life, realize their abilities, learn well and work well, and contribute to their community [7]." The nature of work during the pandemic was in relation to wearing personal protective measures (PPE), the risk of catching the virus and spreading it to others, while delivering handson care for patients, and exposing health workers to various health problems, such as physical, social, and psychological [8]. Scientific evidence confirmed that the outbreak of this disease has caused numerous psychological problems such as pre-and posttraumatic stress disorder (PTSD), anxiety, depression, and anger at a global level [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In hospitals and medical centers, the quality of hospital services will not be guaranteed without the participation of nurses [ 15 ]. Various factors such as incompatibility and dissatisfaction with work, stress, fatigue, illness, and lack of leisure time of nurses affect their behavior [ 16 ]. Nurses who have dealt with patients for a more extended period are more likely to be vulnerable.…”
Section: Introductionmentioning
confidence: 99%